Développer et simplifier A = (x + 3) × 7 B = (x + 5) × 3 - 8 C = (x - 3) × 4 + 2 × x D = 5 × (6 + x) E = 13 × (x - 2) - 4 × 2 × x F = 8 × (x + 5) + (3 + x) × 3 G = x + x + x + (4 - x) × 2 - 5 ×2 H = (2 × x + 3) × 4 I = (3 + 4 × x) × 7 J = 2 × x + 3 × (2 × x - 5) K = 5 × 2 × (5 × x + 7) - 3 × x + 7 × x L = 7 × (x × 3 + 5) + 3 × (5 - 2 × x) M = 2 × (3 × x - 1) × 5 - 2 × x × 4

1

Réponses

2014-01-25T13:22:49+01:00
Bonjour
 A = (x + 3) × 7 = 7x +21
 B = (x + 5) × 3 - 8  = 3x+15 -8 = 3x +7
 C = (x - 3) × 4 + 2 × x = 4x -12 +2x = 6x -12
  D = 5 × (6 + x) = 30 +5x
 E = 13 × (x - 2) - 4 × 2 × x  = 13x - 26 - 8x = 5x -2611x +48

 F = 8 × (x + 5) + (3 + x) × 3 = 8x +40 + 8 +3x = 11x +48
G = x + x + x + (4 - x) × 2 - 5 ×2 = 3x +8 - 2x  -10 = x -2
 H = (2 × x + 3) × 4 =8x +12
 I = (3 + 4 × x) × 7 =( 3 +4x) x 7 = 21 +28x
 J = 2 × x + 3 × (2 × x - 5) = 2x + 3 (2x-5) = 2x +6x -15 = 8x -15
  K = 5 × 2 × (5 × x + 7) - 3 × x + 7 × x  = 10 (5x +7) - 3x +7x = 50x + 70 -3x +7x
 =54x +70
 L = 7 × (x × 3 + 5) + 3 × (5 - 2 × x) = 7(3x +5) +3(5-2x) = 21x +35 + 15 -6x = 15x +50
  M = 2 × (3 × x - 1) × 5 - 2 × x × 4
= 2( 3x -1) (-40 x) = (6x -2 ) (-40x) = -240x² +80x